Penerapan Choice Modelling Pada Taman Wisata Air Kali Medek Di Desa Srimenanti, Lampung Timur - Muhamad Aziz Raynaldi; Toto Gunarto (Journal on Education, 2024)
The aim of writing this journal is to measure the WTP (Willingness To Pay) value of visitors to tourist attractions, analyze what factors influence visitors' choices and to find out the value of the Kali Medek Water Tourism Park in Srimenanti Village, Bandar Sribhawono District, East Lampung Regency based on visitor preferences. This research uses primary data sources and is obtained from distributing questionnaires and interviews. The analytical method used is Wellingness To Pay analysis, Choice Modeling with the variables visit cost (Cost), condition (Cond), education level (Edu), income (Inc), location (Loc) and Total Economic Value. The results obtained in this research are based on primary data, namely the total value of WTP is IDR 99,994,662 in one year. The visit cost variable (Cost) has a positive and insignificant effect on the visitor's choice variable (Choice), the condition variable (Cond) has a positive and significant effect on the visitor's choice variable (Choice), the education variable (Edu) has a positive and significant effect on the visitor's choice variable ( Choice), the income variable (Inc) has a positive and significant effect on the visitor choice variable (Choice), the location variable (Loc) has a positive and significant effect on the visitor choice variable (Choice)